Relationship between Mathematics education philosophy and traditional Malay culture in Serampang 12 - Nina Fadilah; Izwita Dewi; Faiz Ahyaningsih (Inovasi Kurikulum)
Philosophy requires humans to think intelligently to develop towards the next thought of knowledge. The presence of ethnomathematics is not a new thing but has existed since the introduction of mathematics itself as a form of advanced knowledge thinking related to mathematics learning. Through the concept of ethnomathematics, cultural practices can be studied so that students will better understand how their culture is related to mathematics. This study uses a qualitative descriptive research method with a type of ethnographic research that analyzes the movement pattern of traditional Malay dance culture in Serampang 12. The results of the research findings are in the form of variations in mathematics learning, in the form of media associated in the context of traditional Malay culture, so that students who have been considering boring and rigid learning can have a fun lesson because it is associate with the value of the beauty of a Traditional Dance who have a philosophy of politeness, order, togetherness or positive association. The exploration of movement patterns in the traditional dance of Serampang 12 also aims to make it easier for students to build a learning experience that connected to the visual and kinesthetic experience of students.